2004
DOI: 10.1176/appi.psychotherapy.2004.58.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Optimal Adjustment of Interpretation to the Patients’ Level of Defensive Functioning?

Abstract: In this process-outcome study, we explored whether the therapists ' Adjust-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Their work showed that the therapist's adjustment of his or her interventions to the patient's level of defensive functioning could discriminate between high and low alliance dyads, with therapists in the latter group being less adjusted than those in the high alliance dyads. In a second study into therapist adjustment, Hersoug, Hoglend, and Bogwald (2004) used a sample of n = 39 to examine the link between adjustment and alliance building across sessions. Adjustment was calculated the same way as in the Despland and colleagues study (ratio: ESIL/ODF).…”
mentioning
confidence: 99%
“…Their work showed that the therapist's adjustment of his or her interventions to the patient's level of defensive functioning could discriminate between high and low alliance dyads, with therapists in the latter group being less adjusted than those in the high alliance dyads. In a second study into therapist adjustment, Hersoug, Hoglend, and Bogwald (2004) used a sample of n = 39 to examine the link between adjustment and alliance building across sessions. Adjustment was calculated the same way as in the Despland and colleagues study (ratio: ESIL/ODF).…”
mentioning
confidence: 99%
“…In another study, Hersoug et al [75] questioned the earlier notion by Despland et al [71], which assumed that therapist supportive and expressive interventions could be placed on a continuum and then compared to the defense hierarchy. They concluded that what was assumed to be a "poor" adjustment ratio, that is therapist interventions and patient defenses that are not congruent, was actually correlated with a stronger alliance score in some cases.…”
Section: Balance Between Supportive and Interpretive Interventionsmentioning
confidence: 97%
“…This is counterintuitive when we consider that support strategies match with the lower end of the defense continuum to form a more "well adjusted" dyad. Hersoug et al [75] explain this finding by suggesting that because Despland et al [71] studied an ultra-brief form of therapy, it was not necessarily comparable to their naturalistic design, which examined Sessions 7 and 16 of a 40-session treatment.…”
Section: Balance Between Supportive and Interpretive Interventionsmentioning
confidence: 99%
“…Actual research shows that both quality of objects relations and defense mechanisms seem to predict the outcome of therapist's specific technical interventions (Hersoug, Høglend, & Bøgwald, 2004;Piper, Ogrodniczuk, & Joyce, 2004). Consequently, it is recommended that psychotherapy strategies and techniques are based on a careful formulation of the psychodynamics of the patient's presenting complaint, especially when patients with BPD and other personality disorders are treated (Hadjipavlou & Ogrodniczuk, 2010;Verheul & Herbrink, 2007).…”
Section: Intensive-supportive Axis (Is-ax)mentioning
confidence: 99%